Distribution and niche of Suillus aurihymenius in Asia - Vlasenko Vyacheslav (EDP Sciences, 2021)
We defined the regularities spatial distribution of Suillus aurihymenius based on the occurrence data, as well as bioclimatic characteristics in order to control species status in the natural environment. Suillus aurihymenius is a rare species known only from our collections from the Republic of Altai and Republic of Tuva. Realised niche of S. aurihymenius on the western border of its currently known range in larch forests in the floodplains of rivers of the steppe of southeast Altai. Conservation of natural habitats of S. aurihymenius in the steppes of intermontane basins in the southeast of Altai will contribute to its preservation in Russia.